Gelenkschmerzen und Analgetikakonsum bei jungen Leistungssportlern: bundesweite Daten aus dem Jugendbasketball - Schneider, Sven; Berrsche, Gregor (Der Schmerz, 2019)
BackgroundJoint pain may be an early indicator of biomechanical stress. During adolescence the physical development, including the development of the musculoskeletal system, is still ongoing and joint pain requires special attention, especially among young athletes.ObjectiveYoung athletes from the highest national basketball leagues in Germany were questioned about prevalence, location, context and coping strategies concerning joint pain.Material and methodsData were derived from the German “Adolescents’ and Childrens’ Health in Elite Basketball study” (ACHE study). Analyses were based on an online survey of 182 elite basketball players between 13 and 19 years of age from 46 German teams, conducted between April 2016 and June 2016.ResultsIn the highest German leagues 2 out of 3 players suffered from joint pain at the time of the survey (7-day prevalence 64.6%). Pain in the lower extremities occurred most frequently. The 7‑day prevalence for knee and leg pain reached up to 40% and foot pain up to 21%. For 84% of all players, occasional consumption of analgesics was the norm and 40% took them frequently. The consumption of several medicinal substances, especially of cyclooxygenase inhibitors, such as ibuprofen and diclofenac, is widespread among adolescent elite basketball players as 1 out of 7 athletes (13%) used medicinal substances despite being pain-free and 5% used it prophylactically with the purpose of preventing pain.ConclusionFrom the point of view of pain medicine, it is not only the high prevalence of pain that is remarkable but also the widespread use of analgesics without a prescription and the misguided conception of adolescent competitive athletes that such medications have preventive effects.